2005
DOI: 10.4314/wsa.v31i1.5124
|View full text |Cite
|
Sign up to set email alerts
|

Levels of trace metals in water and sediment from Tyume River and its effects on an irrigated farmland

Abstract: Levels of trace metals (Cd, Pb, Co, Zn Cu and Ni) were determined in water and sediment from the Tyume River. Occurrence of these metals in vegetables and soil from a nearby farmland as a result of irrigation with the river water was also investigated. Higher levels of Cd (0.038 ± 0.004 to 0.044 ± 0.003 mg/l) and Pb (0.021 ± 0.004 to 0.035 ± 0.001 mg/l) were found in the river water, which may be detrimental to the "health" of the aquatic ecosystem and the rural communities that utilise the river water for dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 31 publications
5
77
2
Order By: Relevance
“…The analysis of metals in sediment is used for detection of pollutants that may be either absent or in low concentrations in the water column [25,26]. The concentration of metals from the overlying water to the sediment is dependent on a number of external environmental factors such as pH, EC, the ionic strength of the compound, anthropogenic input, the type and concentration of organic and inorganic ligands and the available surface area for adsorption caused by variation in grain size distribution [27].…”
Section: Metals Concentrations In Sedimentmentioning
confidence: 99%
“…The analysis of metals in sediment is used for detection of pollutants that may be either absent or in low concentrations in the water column [25,26]. The concentration of metals from the overlying water to the sediment is dependent on a number of external environmental factors such as pH, EC, the ionic strength of the compound, anthropogenic input, the type and concentration of organic and inorganic ligands and the available surface area for adsorption caused by variation in grain size distribution [27].…”
Section: Metals Concentrations In Sedimentmentioning
confidence: 99%
“…It has also been implicated in endocrine disrupting activities, which could pose serious health problems. Sources of Cd include wastes from Cd-based batteries, incinerators and runoff from agricultural soils where phosphate fertilizers are used since Cd is a common impurity in phosphate fertilizers (Awofolu et al, 2005). The United States Environmental Protection Agency (USEPA) has set a limit of only 0.005 mg/L of Cd (II) for drinking water whereas the WHO guideline value is 0.01 mg/L.…”
Section: Cadmiummentioning
confidence: 99%
“…Cadmium is recognized as one of the most toxic elements with possible human carcinogenic effects (Goering et al, 1994;Awofolu et al, 2005). It accumulates in the kidney and liver leading to chronic kidney dysfunction.…”
Section: Cadmiummentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, if the water is contaminated, it might possibly contaminate the produce cultivated on such land. An earlier study has revealed the influence of surface water on the metallic load of agricultural soil and its produce (Awofolu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%